2017
DOI: 10.5946/ce.2017.010
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Ultrasonography Can Prevent Unnecessary Diagnostic Endoscopic Retrograde Cholangiopancreatography Even in Patients with High Likelihood of Choledocholithiasis and Inconclusive Ultrasonography: Results of a Prospective Study

Abstract: Background/AimsEndoscopic retrograde cholangiopancreatography (ERCP) is the initial therapy recommended for patients with high likelihood of choledocholithiasis. To determine whether endoscopic ultrasonography (EUS) can prevent diagnostic ERCPs in patients with high probability of choledocholithiasis and inconclusive ultrasonography (US).MethodsAll patients with high likelihood of choledocholithiasis and negative US underwent EUS. ERCP was performed for the patients who showed a definite stone/sludge on EUS. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 21 publications
3
6
0
5
Order By: Relevance
“…Para et al found that any of the studied factors such as liver enzymes and ultrasound alone could not be a suitable indicator of stone formation through a study he conducted on 151 patients who underwent ERCP (Parra et al, 2007). In another study on 78 patients performed by Patel et al, they reported that endosonography before operation can decline unnecessary ERCP procedure (Patel et al, 2017).…”
Section: Resultsmentioning
confidence: 97%
“…Para et al found that any of the studied factors such as liver enzymes and ultrasound alone could not be a suitable indicator of stone formation through a study he conducted on 151 patients who underwent ERCP (Parra et al, 2007). In another study on 78 patients performed by Patel et al, they reported that endosonography before operation can decline unnecessary ERCP procedure (Patel et al, 2017).…”
Section: Resultsmentioning
confidence: 97%
“…When MRCP findings are negative in the presence of dilated CBD, EUS provides better visualization of the biliary obstruction because its transducer is close enough to the CBD in the duodenum. Patel et al[23] preferred EUS rather than ERCP as the initial investigation in patients with a probability of choledocholithiasis. Endosonography may also be useful in the evaluation of cholangiocarcinoma[24].…”
Section: Discussionmentioning
confidence: 99%
“…Con el advenimiento de modalidades de imagen menos invasivas, la CPRE ha dejado de ser una herramienta diagnóstica de primera elección y se ha convertido en un procedimiento esencialmente terapéutico 31 . La resonancia magnética y el ultrasonido endoscópico pueden evitar la CPRE en el 30-50% y en el 36-57% de los casos, respectivamente [32][33][34][35][36] .…”
Section: Adecuada Selección Del Pacienteunclassified